Vitamin A supplementation and BCG vaccination at birth may affect atopy in childhood: long‐term follow‐up of a randomized controlled trial. Issue 9 (31st August 2013) - Kiraly, N.; Benn, C. S.; Biering‐Sørensen, S.; Rodrigues, A.; Jensen, K. J.; Ravn, H.; Allen, K. J.; Aaby, P.
Abstract Background Recent evidence suggests that immunogenic interventions such as vaccines and micronutrients may affect atopic sensitization and atopic disease. We aimed to determine whether neonatal BCG vaccination, vitamin A supplementation and other vaccinations affect atopy in childhood. Methods In Guinea–Bissau, low‐birthweight infants were randomized to early (intervention) or delayed (usual policy) BCG. A subgroup was also randomly assigned vitamin A supplementation or placebo in a two‐by‐two factorial design. Participants were followed up at age 3–9 years. The main outcome was atopy defined as skin prick test reaction ≥3 mm. Secondary outcomes were symptoms of eczema, asthma and food allergy. Results Two hundred eighty‐one children had valid skin prick tests performed, and 14% (39/281) were atopic. There was no significant difference in atopy between the early and delayed BCG groups (OR, 0.71; 95% CI, 0.34–1.47). Atopy was significantly reduced in children who had responded to BCG with a scar (OR, 0.42; 0.19–0.94). Vitamin A supplementation was associated with increased atopy (OR, 2.88; 1.26–6.58), especially in those who received simultaneous BCG (5.99; 1.99–18.1, P = 0.09 for interaction between vitamin A supplementation and BCG). Early vs delayed BCG was not associated with symptoms of atopic disease, but vitamin A supplementation increased odds of wheeze within the past 12 months (OR, 2.45; 1.20–4.96). Conclusions There were no statistically significant effects of early vs delayed BCG on atopy or symptoms of atopic disease. Having a BCG scar was associated with reduced atopy, whereas neonatal vitamin A supplementation was associated with increased atopy. Study Registration Clinicaltrials.gov NCT 01420705.